Development of psychology in Soviet Lithuania - Jacikevičius, A. (Psichologija, 1968)
The article is dedicated to commemorating the twenty years of restitution of Soviet power in Lithuania. It discloses some reactionary traits of the idealistic psychology in bourgeois Lithuania and reviews the development of materialist psychology during the first years of the Soviet rule (1940-1941). The post-war period in the development of psychology is subdivided into two stages: 1) the stage of improvement of psychology teaching and improvement of training of psychology professionals (1945-1955); 2) the stage of the research and development of psychology (1956-1965). Fast increase of research in the psychology field in Soviet Lithuania became possible because having restituted the Soviet power, psychology was liberated from various ideological fallacy; second, it was developing as a constituent part of qualitatively new Soviet psychology; third, it was facilitated by the works of numerous outstanding psychologists of the whole Soviet Union; and fourth, it retained the experimental psychology traditions characteristic to it which were formed as early as at the beginning of the 20th century and consolidated in the Soviet years by scientific research and management attempts of the most outstanding figures in Lithuanian psychology J. Vabalas-Gudaitis and A. Gučas.